Effects of water‐misting sprays with forced ventilation on post mortem glycolysis, AMP‐activated protein kinase and meat quality of broilers after transport during summer. (28th December 2015) - Jiang, Nannan; Xing, Tong; Han, Minyi; Deng, Shaolin; Xu, Xinglian
Abstract: Effects of water‐misting sprays with forced ventilation on post mortem glycolysis, adenosine monophosphate‐activated protein kinase (AMPK) and meat quality of broilers after transport during summer were investigated in the present paper. A total of 105 mixed‐sex Arbor Acres broilers were divided into three treatment groups: (i) 45 min transport without rest (T); (ii) 45 min transport with 1 h rest (TR); and (iii) 45 min transport with 15 min water‐misting sprays with forced ventilation and 45 min rest (TWFR). Each treatment consisted of five replicates with seven birds each. The results indicated that the water‐misting sprays with forced ventilation could mitigate the stress caused by transport under high temperature conditions during summer, which reduced the energy depletion in post mortem Pectoralis major (PM) muscle. This resulted in a higher energy status compared to the T group, which would decrease the expression of phosphorylation of AMPK (p‐AMPK). Furthermore, decreased the expression of p‐AMPK then slowed down the rate of glycolysis in post mortem PM muscle during the early post mortem period, which in turn lessened the negative effects caused by transport on meat quality. In conclusion, water‐misting sprays with forced ventilation may be a better method to control the incidence of the pale, soft and exudative meat in broilers.